2015
DOI: 10.1021/acs.energyfuels.5b01307
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Engineering Materials Properties of Fluid-Phase Chemical Hydrogen Storage Materials for Automotive Applications

Abstract: Among candidates for chemical hydrogen storage in PEM fuel cell automotive applications, ammonia borane (AB, NH 3 BH 3 ) is considered to be one of the most promising materials due to its high hydrogen content of 14−16 wt % and high volumetric density of ∼146 g H 2 /liter. To utilize the existing infrastructure, a fluid-phase hydrogen storage material is attractive, and thus, we investigated the materials' properties of AB in liquid carriers for a chemical hydrogen storage slurry system. Slurries composed of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…To develop stable slurry that remains in suspension, we explored preparation methods to obtain homogenous slurry with AB finely dispersed in a liquid carrier. These results are also documented in the literature (Choi et. al.…”
Section: Slurry Developmentsupporting
confidence: 88%
“…To develop stable slurry that remains in suspension, we explored preparation methods to obtain homogenous slurry with AB finely dispersed in a liquid carrier. These results are also documented in the literature (Choi et. al.…”
Section: Slurry Developmentsupporting
confidence: 88%
“…This report details our research findings related to chemical hydrogen storage not only in the narrow context related to ammonia borane and alane but also in the broader, more general context of chemical hydrogen storage materials. This manuscript complements the published works [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ] that put into perspective the challenges of hydrogen storage for automotive applications.…”
Section: Introductionsupporting
confidence: 66%
“…Ammonia borane slurries were prepared with silicone oil (CAS #: 63148−58−3) and Triton X−15 (anti-foaming surfactant, CAS #: 9036−19−5) ranging from 20–50 wt% solids loadings. Choi and Westman investigated preparation methods and optimized the AB slurry to reach up to 50 wt% solid loadings in the silicone oil by reducing particle size and selecting tip-sonication for mixing which was highly beneficial for obtaining well-dispersed slurries and acceptable flowability [ 8 , 9 ].…”
Section: Slurry-phase Dehydrogenation Reactors With Kineticsmentioning
confidence: 99%
“…Based on our previous work to prepare slurries with solid loading of 35−40 wt % (ca. 5.6−6.4 wt % theoretical H 2 ), 17 the production of high-loading slurries was here investigated. In the early phases of this work, slurries with solid loading in excess of 50 wt % (ca.…”
Section: Resultsmentioning
confidence: 99%
“…In our preceding work we optimized AB slurry properties and selected ammonia borane in silicone oil for use as a liquid fuel to provide hydrogen for automotive fuel cell applications. 17 We investigated preparation methods and found that tipsonication is the most beneficial method for obtaining welldispersed slurries and acceptable flow ability obtained with up to 40 wt % (ca. 6.5 wt % H 2 ) loading.…”
Section: Introductionmentioning
confidence: 99%